STARTUPS BRANDING IN ECONOMIC CRISIS: REINVENTING STRATEGIES - YADAV, SAPNA; GUPTA, MOHIT (International Journal of Psychosocial Rehabilitation, 2026)
market and plan of action. But in the situation of economic crisis it is very difficult for any firm to invest huge amount of money on branding, eventually it always comes down to money. It is hard to contend the way that budget directs the strategy. It is a very known fact to all that the success of any business depends on the budgeting strategies. On an average 1000 startups start out their business every year, but only less than 20 percent of that number survive at the end of it. In an already crowded market place setting a startup apart will be crucial to its survival and success. One such example is of uber which practiced “Growth Hacking” in which it gives prominence to its product enhancement instead of its promotion This paper reinvents the outlook of startups for their branding strategies in case of financial dearth.